Efectos antrópicos sobre las praderas sumergidas de carófitos en una laguna cárstica - Alejandro Sosnovsky; Santos Cirujano; Miguel Ángel Cobelas; Miriam Moreno Pérez; Elisa Piña (Anales del Jardín Botánico de Madrid, 2005)
Charophytes are submerged macrophyte algae often found in diverse aquatic habitats. Chara-dominated lakes are typically hard water, calcium-rich and low in phosphate. La Colgada is a 18 m deep, 103 ha small lake located in a tourist area, which has partly resulted in nutrient increases in recent years. Chara hispida var. major (Hartm.) R.D. Wood and Chara hispida f. polyacantha (A. Braun) R.D. Wood meadows are extensive in this ecosystem, but their distribution are influenced by human activities. Negligible densities of C. hispida, always covered by epiphytes, were recorded in the shores adjacent to tourist areas. Horizontal cover and biomass distributions were heterogeneous throughout the lake (0,95 ± 0,55 kg DW•m-2), with minimum values nearby the tourist area (0,68 ± 0,32 kg DW•m-2). Charophyte biomass was inversely related to depth in areas not influenced by anthropogenic impacts. However, that relationship did not occur in anthropized areas. The biomass range of Charophytes in La Colgada lake, 0,22-2,27 kg DW•m-2, was much higher than that recorded in other world lakes and wetlands.